2016
DOI: 10.1007/s11096-016-0296-3
|View full text |Cite
|
Sign up to set email alerts
|

Patient and medication-related factors associated with hospital-acquired hyponatremia in patients hospitalized from heart failure

Abstract: Background Hyponatremia has been known as an important predictor of clinical outcomes in patients with heart failure (HF). While information on hyponatremia in patients with HF has been available abundantly, information on factors associated with increased risk of developing hospital-acquired hyponatremia (HAH) is still limited. Objective To identify patients and medication-related factors associated with HAH in patients hospitalized from HF. Setting Fatmawati Hospital in Jakarta, Indonesia. Methods This is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…Their report details the time course as related to amiodarone use, both with respect to its appearance and its termination. As with the other rare reports of this association (specifically, the 17 cases mentioned in the review by Barham et al and several more I identified 5,6 ), under lying disorders, including heart failure, pulmonary disorders, and the like, have also been present. Nonetheless, with considered deliberation and evaluation, the relationship to amiodarone seems highly likely, though its development in the absence of other underlying patho logies is uncertain.…”
Section: In This Issue Of the Journal Of Innovations In Cardiacsupporting
confidence: 56%
“…Their report details the time course as related to amiodarone use, both with respect to its appearance and its termination. As with the other rare reports of this association (specifically, the 17 cases mentioned in the review by Barham et al and several more I identified 5,6 ), under lying disorders, including heart failure, pulmonary disorders, and the like, have also been present. Nonetheless, with considered deliberation and evaluation, the relationship to amiodarone seems highly likely, though its development in the absence of other underlying patho logies is uncertain.…”
Section: In This Issue Of the Journal Of Innovations In Cardiacsupporting
confidence: 56%
“…Otra opción descrita es el uso concomitante de HBPM con fludrocortisona 10 . Si bien es menos frecuente, el desarrollo de hiponatremia inducida por heparina también está descrito en la literatura, probablemente también mediado por el bloqueo del eje aldosterónico 2,11 . En general, se trata de hiponatremias leves, no menores de 130.…”
Section: Discussionunclassified
“…As diuretics excrete sodium and the water goes with the sodium, plus the inhibition of aldosterone release and antagonism of its action, we find one easy explanation for the growing interest in hyponatremia as a frequently missed condition. This "depletional" form of hyponatremia occurs at serum sodium levels much closer to what is regarded as "normal," frequently identified with levels around 130-135 mmol/l, which is very different from the "dilutional" form seen with the syndrome of inappropriate antidiuretic hormone secretion produced by medications such as the selective serotonin reuptake inhibitors where levels of 118-125 mmol/l are common (Saepudin et al, 2015;2016).…”
Section: Dr Hana Morrissey and Prof Patrick Ballmentioning
confidence: 95%